DAKWAH TRANSFORMATIF DALAM PEMBERDAYAAN EKONOMI UMMAT DI DURI - Haryanto, Rudi; Azzahra, Nabila; Chairiah Aulia Anwar (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2026)
Abstract. This research is motivated by the low level of economic independence among the Muslim community in Duri City, Riau, which is still dominated by the informal sector, limited access to capital, and a lack of literacy in sharia-based entrepreneurship. The study aims to analyze the role of transformative da'wah in fostering sustainable economic empowerment of the ummah. A qualitative descriptive method was employed, using data collection techniques such as observation, in-depth interviews with religious leaders, mosque managers, and small business actors, as well as documentation of ongoing empowerment programs. The results show that transformative da'wah functions not only as a means of conveying spiritual values but also as a driver of social change through entrepreneurship training, the formation of community-based cooperatives, and the productive distribution of zakat. This approach encourages active community participation in building economic self-reliance based on Islamic principles, although challenges remain in terms of coordination, mentoring, and limited human resources. Abstrak. Penelitian ini dilatarbelakangi oleh lemahnya kemandirian ekonomi umat di Kota Duri, Riau, yang masih didominasi oleh sektor informal, keterbatasan akses modal, dan rendahnya literasi kewirausahaan berbasis syariah. Penelitian ini bertujuan untuk menganalisis peran dakwah transformatif dalam membangun pemberdayaan ekonomi umat secara berkelanjutan. Metode yang digunakan adalah kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara mendalam dengan tokoh agama, pengelola masjid, pelaku UMKM, serta dokumentasi program-program pemberdayaan yang berjalan. Hasil penelitian menunjukkan bahwa dakwah transformatif tidak hanya berperan sebagai media penyampaian nilai-nilai spiritual, tetapi juga menjadi penggerak perubahan sosial melalui pelatihan wirausaha, pembentukan koperasi jamaah, dan pengelolaan zakat produktif. Pendekatan ini mendorong partisipasi aktif masyarakat dalam membangun kemandirian ekonomi berbasis nilai Islam, meskipun masih menghadapi tantangan dalam aspek koordinasi, pendampingan, dan keterbatasan sumber daya manusia.